2023
DOI: 10.1097/as9.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insurance Type With Inpatient Surgical 30-Day Readmissions, Emergency Department Visits/Observation Stays, and Costs

Abstract: Objective: To assess the association of Private, Medicare (MC), and Medicaid/Uninsured (MU) insurance type with 30-day emergency department visits/observation stays (EDOS), readmissions, and costs in a safety-net hospital (SNH) serving diverse socioeconomic status patients. Background: MC’s hospital readmission reduction program (HRRP) disproportionately penalizes SNHs. Methods: This retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…However, alleviating these disparities requires metrics to target reducing this greater comorbidity burden. Explanation 2 requires analyzing longer-term outcomes than typically captured by surgical studies . While the discrepancy between racial disparities in 30-day mortality vs DOOR requires further investigation, we nonetheless suggest focusing resources on preventive care to reduce presentation acuity among veterans identified as Black, as acuity seems to be a key driver in outcome disparities for Black veterans.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, alleviating these disparities requires metrics to target reducing this greater comorbidity burden. Explanation 2 requires analyzing longer-term outcomes than typically captured by surgical studies . While the discrepancy between racial disparities in 30-day mortality vs DOOR requires further investigation, we nonetheless suggest focusing resources on preventive care to reduce presentation acuity among veterans identified as Black, as acuity seems to be a key driver in outcome disparities for Black veterans.…”
Section: Discussionmentioning
confidence: 90%
“…These disparities, studied across various health care domains, are critically important in surgical care, as even minor surgery can sometimes include serious risk . Moreover, SDOH are incredibly varied: Black patients can have 1.2 to 1.5 times higher surgical mortality vs White patients, patients living in areas labeled by the US Government Home Owners Loan Corporation as historically “hazardous” neighborhoods can have 1.19 times higher mortality than those living in areas labeled the “best” neighborhoods, and insurance type (means-tested insurance like Medicaid or no insurance) drives greater urgent and emergent surgical procedures, complications, readmissions, and lengths of hospital stay . All this prior work suggests that multiple SDOH need to be evaluated simultaneously, not in isolation, because SDOH can have independent effects or be heavily confounded with each other …”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with another study from the USA that showed Medicare self-paid patients had 24% higher odds of developing complications. 42 In this regard, working toward attaining universal health coverage is imperative for reducing financial risk and ensuring the provision of essential healthcare services for all, including vulnerable populations. 39 Our results showed that the CCI score was associated with mortality in EGS patients.…”
Section: Open Accessmentioning
confidence: 99%